On Relativization and Clefting : an Analysis of Italian Sign Language - Branchini, Chiara (Sign languages and deaf communities, 2014)
This work is a contribution to our understanding of relativization strategies and clefting in Italian Sign Language, and more broadly, to our understanding of these constructions in world languages by setting the discussion on the theories that have been proposed in the literature of spoken languages to derive the syntactic phenomena object of investigation.